Dynamics and socio-environmental impacts of mopane worm harvesting in rural communities in Zimbabwe: prospects for climate-smart approaches - Dube, Susan Samukele; Chitakira, Munyaradzi (Frontiers in Sustainability, 2024)
Rural communities in parts of Botswana, Namibia, South Africa, and Zimbabwe rely heavily on mopane worms (imbrasia belina) as a livelihood, particularly during times when the households have limited livelihood options. While mopane worms are a vital source of protein and income for rural communities, climate change and variability are putting the sustainability of this vital natural resource under threat. As such, a critical evaluation of the harvesting methods and the associated dynamics is necessary to establish ways of sustaining this resource. This study thus sought to examine the existing mopane worm harvesting practices and evaluate their viability in the wake of climate change and variability. The study focused on Garanyemba Ward 13 of Gwanda District in south-western Zimbabwe. It assessed the harvesting practices and their impact on the environment and the sustainability of mopane worm populations. A qualitative research approach involving participant observation, focus group discussions, and interviews was employed. The findings show that the harvesting of mopane worms in the area was achieved predominantly through climbing up or shaking the trees, plucking worms from branches, and gathering worms that would otherwise be crawling on the ground. Socio-environmental impacts of the existing methods of harvesting revealed include vegetation damage leading to decreased mopane woodland densities, the emergence of squatter communities during outbreak times and the associated land pollution. The study concludes that the influx of foreign harvesters, which eventually exposed the habitat of mopane worms over-harvesting was attributed to limited institutional control. The study recommends control of harvesters by strick enforcement of regulatory frameworks, adherence to selective harvesting to ensure the preservation of worms for future production.